Geographical segregation and IL-6: a marker of chronic inflammation in older adults - Purser, Jama L; Kuchibhatla, Maragatha N; Miranda, Marie L; Blazer, Dan G; Cohen, Harvey J; Fillenbaum, Gerda G (Biomarkers in medicine, 2008)
To examine environmental sociodemographic risks of high IL-6, a marker of chronic inflammation in older adults. We spatially linked 1990 USA Census tract demographic and economic measures to a prospective cohort study of representative community residents aged  71  years and older, from over  1700 of whom a cytokine protein and biological marker of chronic inflammation, IL-6, was collected. Using generalized interactive mixed models, we modeled 1989-–1990 individual and census level risk factors for the dependent variable high IL-6 between 1992-–1993 (high IL-6  =  upper quartile: >2.96  pg/ml). After individual health risk adjustment, IL-6 remained elevated in communities with greater densities of poor older adults (odd ratio [OR]: 1.25 per 10% increase in exposure, 95% confidence interval [CI]:  1.05, 1.48) and in racially segregated communities (OR: 1.14 per 10% increase in exposure, 95% CI:  1.04, 1.25). Socially disadvantaged environments may influence IL-6, a biomarker of age-associated inflammation.